A study on smart parking system using IOT technology in shopping mall - Goh, Yuki (2023)
Smart parking system with IoT technology is important in shopping mall parking because it enhances convenient and efficiency to the shoppers and visitors. The system can assist to reduce several problems that impacted to the users, such as wasting time in finding parking and paying parking fees at auto-pay machine. Thus, this research was conducted to study on the components of smart parking system that will affect the level of customer’s satisfaction. The components include smart payment system, sensor system, navigation system, security system, parking reservation system and electric vehicle charging system. Questionnaires were used to collect data with total respondents of 100 who are above 16 years old and has experience driving vehicles to shopping mall in Kuala Lumpur. The results obtained from Relative Important Index analysis shown the most affecting component of smart parking system was smart payment system. Therefore, the shopping operator, developer and property manager can emphasize the most important elements of the smart parking system to enhance the management and increase the customer’s satisfaction. In addition, the smart parking system should be implemented in Malaysia to ensure that the parking system has advanced and comprehensive facilities to the visitors.